Flash spark plasma sintering of 3YSZ. Issue 5 (May 2019) - Biesuz, Mattia; Sedlák, Richard; Saunders, Theo; Kovalčíková, Alexandra; Dusza, Ján; Reece, Mike; Zhu, Degui; Hu, Chunfeng; Grasso, Salvatore
Abstract: Flash SPS (FSPS) consolidation of 3YSZ cold pressed pellets was investigated. The results show that FSPS allows ultra-rapid consolidation of 3YSZ samples in 30–90 s under an applied electric field. The DC field induces electrochemical blackening. The partial reduction process starts from the cathode (-) and propagates toward the anode (+). This phenomenon, not previously discussed in FSPS literature, induces the development of internal temperature gradients resulting in a polarity dependent grain size/densification.